2011
DOI: 10.1038/ijo.2011.12
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of inflammation-associated factors by indole-3-carbinol in mice fed high-fat diets and in isolated, co-cultured macrophages and adipocytes

Abstract: Aims:This study investigated the effects of indole-3-carbinol (I3C), a compound from cruciferous vegetables, on various parameters related to obesity, in particular, the parameters of infiltration by macrophages and of inflammatory cytokines expressed during the co-culture of adipocytes and macrophages.Methods:Male C57BL/6 mice were fed with a control diet (C group), high-fat diet (HF group) and HF+5 mg kg−1 I3C (HFI group). The I3C was intraperitoneally injected (HFI group) for 12 weeks. Epididymal adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 44 publications
1
28
0
2
Order By: Relevance
“…The increased accumulation of macrophages in the epididymal adipose tissue of mice fed high-fat diets was reduced with i.p. injections of I3C, and in vitro studies also showed that I3C mixed in co-cultures of macrophages and adipocytes, led to decreases in inflammatory factors, IL-6 and nitrite production (Chang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The increased accumulation of macrophages in the epididymal adipose tissue of mice fed high-fat diets was reduced with i.p. injections of I3C, and in vitro studies also showed that I3C mixed in co-cultures of macrophages and adipocytes, led to decreases in inflammatory factors, IL-6 and nitrite production (Chang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Since BC and its primary metabolite DIM recently have been shown to produce anti-inflammatory and immunoregulatory effects in vitro (16)(17)(18)22), these compounds have the potential to elicit protective effects in diseases characterized by chronic inflammation. The current conventional medicines for Crohn's disease, a chronic inflammatory disease of the gastrointestinal tract, can be accompanied by severe adverse effects so many patients have turned towards natural and complementary therapies as part of their treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…For histological analysis, a I cm section from the distal colon was fixed in 2% paraformaldehyde, processed in the Shandon Citadel 2000 Automated Tissue Processor (Thermo Fisher Scientific, Waltham, MA) with vacuum unit, embedded using the Shandon Histocentre 2 Embedding unit, sectioned at 7 urn using the Thermo Shandon Finesse 325 microtome, and stained with hematoxylin and eosin (H&E) in the Shandon Veristain 24-4 Slide Stainer. Colons were assessed microscopically by a blinded individual to determine the severity of inflammation based on an established scoring table (16). Briefly, colon damage was based on a combination of the severity of inflammatory cell infiltration into the tissue and the severity of tissue lesions.…”
Section: Colon Processing and Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in this model I3C did not show protective effects. When male C57BL/6 mice received a HFD and were treated intraperitoneally with I3C for 12 weeks, this resulted in a profound improvement of metabolic inflammation in adipose tissue by the substantial decrease of macrophage infiltration and their cytokine production [21].…”
Section: Further Beneficial Examples For Indole Derivativesmentioning
confidence: 99%